Taphonomy of Biosignatures in Microbial Mats on Little Ambergris Cay, Turks and Caicos Islands - Gomes, Maya L.; Riedman, Leigh Anne; O’Reilly, Shane; Lingappa, Usha; Metcalfe, Kyle; Fike, David A.; Grotzinger, John P.; Fischer, Woodward W.; Knoll, Andrew H. (Frontiers in Earth Science, 2020)
Microbial mats are taxonomically and metabolically diverse microbial ecosystems, with a characteristic layering that reflects vertical gradients in light and oxygen availability. Silicified microbial mats in Proterozoic carbonate successions are generally interpreted in terms of the surficial, mat building community. However, information about biodiversity in the once-surface-layer can be lost through decay as the mats accrete. To better understand how information about surface microbial communities is impacted by processes of decay within the mat, we studied microbial mats from Little Ambergris Cay, Turks and Caicos Islands. We used molecular techniques, microscopy and geochemistry to investigate microbial mat taphonomy – how processes of degradation affect biological signatures in sedimentary rocks, including fossils, molecular fossils and isotopic records. The top < 1 cm of these mats host cyanobacteria-rich communities overlying and admixed with diverse bacterial and eukaryotic taxa. Lower layers contain abundant, often empty, sheaths of large filamentous cyanobacteria, preserving their record as key mat-builders. Morphological remains and free lipid biomarkers of several bacterial groups, as well as diatoms, arthropods, and other eukaryotes also persist in lower mat layers, although at lower abundances than in surface layers. Carbon isotope signatures of organic matter were consistent with the majority of the biomass being sourced from CO2-limited cyanobacteria. Porewater sulfide sulfur isotope values were lower than seawater sulfate sulfur isotope values by ∼45–50‰, consistent with microbial sulfate reduction under sulfate-replete conditions. Our findings provide insight into how processes of degradation and decay bias biosignatures in the geological record of microbial mats, especially mats that formed widely during the Proterozoic (2,500–541 million years ago) Eon. Cyanobacteria were the key mat-builders, their robust and cohesive fabric retained at depth. Additionally, eukaryotic remains and eukaryotic biosignatures were preserved at depth, which suggests that microbial mats are not inherently biased against eukaryote preservation, either today or in the past.